Collective Action Outcomes: Ways Forward for the Subfield - Bosi, Lorenzo; Uba, Katrin (PARTECIPAZIONE E CONFLITTO, 2021)
Given the growing interest in how collective action matters, this special issue seeks to push our understanding of collective action outcomes beyond the present state of knowledge and stimulate further developments. In doing this, it looks to improve and expand the theoretical and conceptual tools for studying the topic, suggest and explore methodological innovations to solve previous research problems and investigate new settings across various movements and countries.